Evaluation of Diagnostic Accuracy of Anal Fistula by 360° Endoanal Ultrasound - Singha, Jawhar Lal; Ahmad, Sami; Ahmed, Nadim; Nayeem, SM Zulker; Rayhan, Ferdoush; Ahmed, Farhad Uddin (Journal of Shaheed Suhrawardy Medical College, 2019)
Introduction: 360° endoanal ultrasound (EAUS) has become an effective imaging tool to diagnose anal fistulas for last three decades. Objectives: To assess the diagnostic accuracy of 360° endoanal ultrasound imaging comparing pre and peroperative diagnosis in anal fistulas. Methods: Between Jauary 2015 and June 2018, 240 patients with clinical anal fistula underwent endoanal sonographic assessment using a 360° endoanal transducer (7–15 MHz The sonographic findings, including the fistulas and other inflammatory lesions, were correlated with surgical results. The types of fistulas on endoanal sonography based on classification of Park and the internal opening of the fistula, both pre and peroperative, were compared to those of other studies. Results: The 240 patients studied included 165 male and 75 female patients. Endoanal sonography was able to show and track hypoechoic lesions, their locations, and internal openings of the fistulas. Compared with surgical results, endoanal sonography had sensitivity of 94.6%, specificity of 100%, and accuracy of 94.1% for the diagnosis of perianal fistulas. Also, endoanal sonography had accuracy of 86.1% for determining fistula types based on the Parks classification and 92.8% for identifying internal openings of the fistulas. Conclusions: Endoanal ultrasound is an accurate and noninvasive imaging modality for evaluation of fistulas. It is a very useful tool for preoperative management and surgical planning by providing precise and detailed information on fistulas. J Shaheed Suhrawardy Med Coll, December 2018, Vol.10(2); 66-69